Anatomy of Sudden Yen Appreciations - Han, Fei (IMF Working Papers; Working Paper ;, 2019)
The yen is an important barometer for the Japanese economy. Depreciations are typically associated with favorable economic developments such as increased corporate profits, rising equity prices, and upward pressure on domestic consumer prices. On the other hand, large and sharp appreciations run the risk of lowering actual and expected inflation, squeezing corporate profits, generating a negative wealth effect through depressed equity prices, and reducing confidence in the Bank of Japan's efforts to reflate the domestic economy and achieve the inflation target. This paper takes a closer look at underlying drivers of rapid yen appreciations, highlighting the key role of carry-trade and the zero lower bound as important amplifiers.